COVID-19: A Syndemic Requiring an Integrated Approach for Marginalized Populations - Caron, Rosemary M.; Adegboye, Amanda Rodrigues Amorim (Frontiers in Public Health, 2021)
The novel coronavirus, SARS-CoV-2, responsible for the COVID-19 pandemic, has challenged healthcare systems globally. The health inequities experienced by immigrants, refugees, and racial/ethnic minorities have been aggravated during the COVID-19 pandemic. The socioeconomic, political, and demographic profile of these vulnerable populations places them at increased risk of contracting COVID-19 and experiencing significant morbidity and mortality. Thus, the burden of the COVID-19 pandemic is disproportionally higher among these at-risk groups. The purpose of this perspective is to: (1) highlight the interactions among the social determinants of health (SDoH) and their bi-directional relationship with the COVID-19 pandemic which results in the current syndemic and; (2) offer recommendations that consider an integrated approach to mitigate COVID-19 risk for marginalized populations in general. For these at-risk populations, we discuss how individual, structural, sociocultural, and socioeconomic factors interact with each other to result in a disparate risk to contracting and transmitting COVID-19. Marginalized populations are the world's collective responsibility. We recommend implementing the Essential Public Health Services (EPHS) framework to promote those systems and policies that enable optimal health for all while removing systemic and structural barriers that have created health inequities. The pledge of “Health for All” is often well-accepted in theory, but the intricacy of its practical execution is not sufficiently recognized during this COVID-19 syndemic and beyond.